2021
DOI: 10.3389/fclim.2021.643224
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Work and Interpretations in the IPCC Review Process of the Role of Bioenergy With Carbon Capture and Storage (BECCS) in Limiting Global Warming to 1.5°C

Abstract: Paris Agreement-compatible emissions pathways produced by integrated assessment models (IAMs) often rely on large amounts of carbon dioxide removals, especially afforestation and bioenergy with carbon capture and storage (BECCS). These pathways feature prominently in the work of the Intergovernmental Panel on Climate Change (IPCC), to the extent that the IAMs have been granted an interpretative privilege at the interface between climate science, economics, and policymaking. The privilege extends to and influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…A cut-off date for publishing this new research was set by the IPCC. Nevertheless, during the review process of SR15, it became apparent that the lack of available literature, alongside the specific mandate to focus on 1.5 C of warming, limited the framing of the report (see Hansson et al, 2021), and the technological pathways to achieve this goal that the report identified. The example of SR15 illustrates the tight connection the IPCC has with the scientific and social scientific communities upon whose work it bases its assessments (see also Chapter 12).…”
Section: Framing Products In Changing Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…A cut-off date for publishing this new research was set by the IPCC. Nevertheless, during the review process of SR15, it became apparent that the lack of available literature, alongside the specific mandate to focus on 1.5 C of warming, limited the framing of the report (see Hansson et al, 2021), and the technological pathways to achieve this goal that the report identified. The example of SR15 illustrates the tight connection the IPCC has with the scientific and social scientific communities upon whose work it bases its assessments (see also Chapter 12).…”
Section: Framing Products In Changing Contextsmentioning
confidence: 99%
“…Hansson, A., Anshelm, J., Fridal, M., and Haikola, S. (2021). Boundary work and interpretations in the IPCC review process of the role of bioenergy with carbon capture and Storage (BECCS) in limiting global warming to 1.5 C. Frontiers in Climate, 3: 643224. http://doi.org/10.3389/fclim.2021.643224This article is one of the few close studies of IPCC peer review of a particular issue.…”
mentioning
confidence: 99%
“…In the UK, the actual realisation of large-scale BECCS to date has been stymied by significant costs associated both with capturing CO 2 and with developing infrastructures capable of achieving its safe, long-term storage. Recent research, moreover, has pointed to considerable expert "dissatisfaction" with a continuing tendency for BECCS to be presented as a viable carbon dioxide removal strategy at large scales (Hansson et al, 2021), as well as to divergent stakeholder interpretations of what it might mean to incentivise BECCS responsibly in practice (Bellamy et al, 2021). Nonetheless, for one influential contingent of UK-based industry organisations, scientific researchers and start-up firms, concerns about BECCS can be overcome by treating CO 2 not as a waste product per se, but as a valuable economic resource in its own right.…”
Section: Beccus: "Turning Pollution Into Possibilities"?mentioning
confidence: 99%
“…A common result based on IAMs is that large point sources of biogenic emissions such as energy utilities could implement BECCS on a large-scale globally in the coming decades (IPCC, 2018;Rogelj et al, 2018a), but the industrial sector (e.g., steel, cement, paper, ethanol, and chemicals) is also a strong contender for BECCS as well as a source of residual emissions (Tanzer et al, 2021). However, there are concerns about trade-offs between the UN's Sustainable Development Goals (SDGs) and large-scale deployment of BECCS, such as using arable land for bioenergy crops impacting biodiversity, water, forests, and food security (Hansson et al, 2021;Rogelj et al, 2018b;United Nations, 2015). Other factors that are crucial for deploying BECCS are geographical proximity to prospective storage sites, storage uncertainties, and public and political acceptance including enabling policies, although these factors are rarely considered by IAMs (Hansson et al, 2021;Janipour et al, 2021;Lane et al, 2021).…”
Section: Introductionmentioning
confidence: 99%